Особливості взаємозв’язку когнітивних схем та психологічного благополуччя працівників поліції - Красуля, О. М.; Krasulia, O. M. (Габітус. - 2024. - Вип. 59. - С. 156-160, 2024)
У статті здійснено аналіз кореляційного зв’язку когнітивних схем із психологічним благополуччям працівників поліції. Психологічне благополуччя працівників поліції безпосередньо впливає на їх продуктивність, здатність до командної роботи, відновлення після стресових подій і загалом на якість виконання службових обов’язків. Негативне сприйняття себе як професіонала, страх помилки або надмірна самокритичність можуть помітно знизити ефективність роботи поліцейського. Усвідомлення та керування власними когнітивними процесами є ключовим для підтримання психологічного здоров’я та ефективності роботи працівників поліції.

The article analyzes the correlation between cognitive schemes and the psychological well-being of police officers. The psychological well-being of police officers directly affects their productivity, ability to work as a team, recovery from stressful events and, in general, the quality of performance of official duties. A negative perception of oneself as a professional, fear of making a mistake or excessive self-criticism can significantly reduce the effectiveness of a police officer. Awareness and m anagement of one’s own cognitive processes is key to maintaining the psychological health and efficiency of police officers. The purpose of the study was to study the corellation between psychological well-being and cognitive patterns of police officers. 150 police officers between the ages of 25 and 50 took part in the study. Psychodiagnostic methods were used to conduct the study, which are adequate for the purposes of the study: “Scale of psychological well-being” by K. Riff (adapted by T. Shevelenkova, P. Fesenko) and “Scale of basic beliefs” by R. Yanov-Bulman (adapted by O. Kravtsova). To assess the statistical significance of the study, the Pearson correlation test was used. The article outlines the importance of studying the relationship between cognitive schemas and psychological well-being of police officers in order to improve and facilitate their service. Cognitive schemas are generalized mental structures that help organize experience and manage perception of the surrounding world, shaping behavior and emotional reactions to various situations. This allows police officers to quickly interpret situations, make decisions and act. This is important when performing complex and unpredictable tasks. It is noted that the high level of well-being of police officers, that is, life satisfaction, emotional balance and the absence of long-term negative emotional states, largely depends on how their cognitive schemes interpret the surrounding reality and how flexibly they can adapt to changes in their environment. Police officers whose cognitive schemes are oriented towards positive perception and assessment of situations have more chances to achieve a high level of psychological well-being. As a result, they perform their duties more efficiently, are less prone to emotional burnout and cope better with work-related stress.

В статье проведен анализ корреляционной связи когнитивных схем с психологическим благополучием работников полиции. Психологическое благополучие работников полиции оказывает непосредственное влияние на их производительность, способность к командной работе, восстановление после стрессовых событий и в целом на качество исполнения служебных обязанностей. Негативное восприятие себя как профессионала, страх ошибки или чрезмерная самокритичность могут заметно снизить эффективность работы полицейского. Осознание и управление собственными когнитивными процессами является ключевым для поддержки психологического здоровья и эффективности работы сотрудников полиции.
Features of the correlation of cognitive schemes and psychological well-being of police employees
Keywords: когнітивні схеми; психологічне благополуччя; працівники поліції; задоволення життям; базові переконання; cognitive schemas; psychological well-being; police officers; life satisfaction; basic beliefs; когнитивные схемы; психологическое благополучие; работники полиции; удовлетворение жизнью; базовые убеждения